PENGARUH ALGAE MERAH (EUCHEUMA SPINOSUM) TERHADAP INFEKSI ESCHERICHIA COLI - Putu Urvasi Ari Utami; Ety Apriliana; Rika Lisiswanti; Liana Sidharti (CV. Jasa Sukses Abadi, 2023)
Bacteria can contribute to the development of diarrheal disease through direct contact with those who have the condition, consumption of food and drink contaminated with feces, or both. In addition, water, food sanitation, family latrines are the main causes of diarrheal disease. Among the causative bacteria, Escherichia coli is the most common pathogen for diarrhea in children in developing countries and an associated entero-pathogen of emerging antimicrobial resistance in developed countries. Reports of increased antibacterial resistance have become a challenge in handling diarrhea cases. Eucheuma spinosum is a species of red algae which is a marine organism that has been screened for phytochemicals and found to contain active substances such as flavonoids, triterpenoids, alkaloids, and ascorbic acid. Phenol compounds and their derivatives (flavonoids) are predicted to be compounds in E. spinosum that have the potential to inhibit E. coli bacteria by damaging the bacterial cytoplasmic wall.